The carrier AUXIN RESISTANT (AUX1) dominates auxin flux into Arabidopsis protoplasts. Issue 3 (16th July 2014) - Rutschow, Heidi L.; Baskin, Tobias I.; Kramer, Eric M.
Summary: The ability of the plant hormone auxin to enter a cell is critical to auxin transport and signaling. Auxin can cross the cell membrane by diffusion or via auxin‐specific influx carriers. There is little knowledge of the magnitudes of these fluxes in plants. Radiolabeled auxin uptake was measured in protoplasts isolated from roots of Arabidopsis thaliana . This was done for the wild‐type, under treatments with additional unlabeled auxin to saturate the influx carriers, and for the influx carrier mutant auxin resistant 1 ( aux1 ). We also used flow cytometry to quantify the relative abundance of cells expressing AUX1‐YFP in the assayed population. At pH 5.7, the majority of auxin influx into protoplasts – 75% – was mediated by the influx carrier AUX1. An additional 20% was mediated by other saturable carriers. The diffusive influx of auxin was essentially negligible at pH 5.7. The influx of auxin mediated by AUX1, expressed as a membrane permeability, was 1.5 ± 0.3 μm s −1 . This value is comparable in magnitude to estimates of efflux permeability. Thus, auxin‐transporting tissues can sustain relatively high auxin efflux and yet not become depleted of auxin.